Pengaruh Perlindungan Propolis Terhadap Tukak Lambung Tikus Putih (Rattus norvegicus) Jantan Galur Wistar yang Diinduksi Ibuprofen - Yasli , Afifah Salsabila; Rahayu , Mulyati Sri; Siregar , Sarah Rahmayani (Journal of Pharmaceutical and Sciences, 2025)
Background: The use of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) such as ibuprofen often associated with gastric mucosal damage commonly referred to as gastric ulcer. This damage occurs due to the inhibition of the cyclooxygenase (COX) enzyme, which plays a cytoprotective role. Propolis, a natural product from honeybees, is known to contain flavonoids with anti-inflammatory, antioxidant, and anti-ulcer activities that can protect the gastric mucosa. Objective: This study aimed to determine the protective effect of propolis against gastric ulcers in male Wistar rats (Rattus norvegicus) induced by ibuprofen. Methods: True Experimental method with a Post-Test Only Control Group Design. The sample consisted of 30 male Wistar rats divided into five groups: a control group without treatment, a negative control group treated with ibuprofen 400 mg/kg, and three treatment groups administered propolis doses of 0.13 ml, 0.26 ml, and 0.52 ml. The treatment was conducted for the first seven days, followed by ibuprofen induction at 400 mg/kg for the next seven days. Results: The lowest mean number and severity of ulcers were found in the P3 group (3.1 ± 0.75; 2.4 ± 0.48). The Kruskal Wallis test results indicated a significant difference in the number and severity of ulcers between the control and treatment groups (p < 0.05). However, the post hoc Mann Whitney test revealed no significant differences among the treatment groups (p > 0.05). Conclusion: Propolis administration reduced the number and severity of ulcers caused by ibuprofen induction. Nevertheless, the dose of propolis used in this study have not yet achieved optimal efficacy